Bearing capacity of mixed soil model - Abdoullah Namdar; Mehdi Khodashenas Pelkoo (Fracture and Structural Integrity)
The main objective of this research is the improvement of red soil by the addition of construction materials. This method could provide a scientific way to create a soil foundation with sufficient stability against geo-technical problems or instabilities. Laboratory tests have been conducted to characterize the behavior of red soil when amended with different types of gravels, soils and sand under compacted conditions with Optimum Moisture Content (OMC). Safe bearing capacity of all models have been calculated to identify the best and worst soil mixed model.